PERBEDAAN BENTUK DAN UKURAN RUGAE PALATINA ANTARA AYAH DAN ANAK KANDUNG LAKI-LAKI SUKU MINANGKABAU DI WILAYAH LUHAK NAN TIGO - Nada Rania; Nila Kusuma; Murniwati Murniwati (Andalas Dental Journal, 2018)
Palatal rugae or plica palatinae transversae are irregular and asymmetrical ridges on mucosa membrane which extend laterally from incisive papilla and anterior of palatal raphe. Palatal rugae are protected by cheeks, lips, tongue and buccal pad from incineration and trauma. The use of palatal rugae as an alternative way to identify human is needed in many occurrences such as accident, criminal and disaster. Palatal rugae patterns are vary and not identical in each person but have some similarities within family. This can be caused by hereditary and polygenic inheritance mechanism of palatal rugae. This study aimed to identify palatal rugae pattern similarities between father and his biological son in Minangkabau ethnic. This study is a cross-sectional study. The samples used in this study were 78 pairs of fathers and their biological sons. Alginate impression material was used to record the upper jaw. The impressions were casted by type III dental stone . Palatal rugae were marked and the amount of rugae based on their shape and length classifications were recorded. The data were analyzed using Mann -Whitney test. Result showed that there was no significant difference between fathers’ and their biological sons’ palatal rugae amount based on their shape (p>0,05), but there was significant difference between the amount of primary rugae of fathers and their biological sons (p<0,05). The conclusion is there are no significant differences between fathers’ and th eir biological sons’ palatal rugae amount based on their shape. Palatal rugae pattern can be used as an alternative in human identification because of its individual characteristic and uniqueness. Keywords: palatal rugae, Minangkabau ethnic, father and biological son